Mediación directiva y su influencia en el desarrollo de las actividades académicas de los estudiantes de 5to año de Educación Básica de la escuela Leónidas Plaza Gutiérrez del Recinto La Lucha del cantón Baba provincia Los Ríos del periodo lectivo 2018- 2019 - Vargas Mora, Viviana Lorena (2020)
The managerial mediator must be a strategist, globalizer of goals, ideas and programs, a generator of programmed activities and processes that allows the fulfillment of the purposes of the educational center, which do not refer only to the pedagogical function in the classroom, but also to its link with the environment, the appropriate school organization encompassed within a comprehensive management that promotes the strengthening of educational quality in the institution, given that education is a determining factor in the formation of human talent, it is a system of dynamization, support and Accompaniment to pedagogical and institutional action is the participatory, planned and organized process through which the director, as pedagogical leader and manager of the educational center, guides, motivates, involves and is accountable to the educational community, in such a way that all efforts and wills are based on achieving better learning.